Synthesis, crystal structure, Hirshfeld surface analysis and DFT calculations of the coordination compound tetraaquabis{2-[(5-methyl-1,3,4-thiadiazol-2-yl)sulfanyl]acetato-κO}cobalt(II) - Ekaterina Kinshakova; Batirbay Torambetov; Simranjeet Kaur; Jamshid Ashurov; Shakhnoza Kadirova (Acta Crystallographica Section E: Crystallographic Communications)
A novel coordination compound, [Co(L)2(H2O)4], was synthesized from aqueous solutions of Co(NO3)2 and the ligand 2-[(5-methyl-1,3,4-thiadiazol-2-yl)sulfanyl]acetic acid (HL, C5H6N2O2S2). In the monoclinic crystals (space group P21/c), the cobalt(II) ion is located about a centre of symmetry and is octahedrally coordinated by two L− anions in a monodentate fashion through carboxyl O atoms and by four water molecules. A relatively strong hydrogen bond between one of the water molecules and the non-coordinating carboxylate O atom consolidates the conformation. In the crystal, intermolecular hydrogen bonds lead to the formation of a complex tri-periodic structure. Hirshfeld surface analysis revealed that 30.1% of the intermolecular interactions are from H...H contacts and 20.8% are from N...H/H...N contacts. DFT calculations were performed to assess the stability and chemical reactivity of the compound by determining the energy differences between the HOMO and LUMO.